Original paperFrequency of use of ECG teletransmission in pre-hospital management of patients with suspected acute myocardial infarction – effects of POLKARD pilot programme in eastern Masovia - Karcz, Maciej; Bekta, Paweł; Skwarek, Mirosław; Dąbrowski, Maciej; Kukuła, Krzysztof; Przyłuski, Jakub; Kądziela, Jacek; Kruk, Mariusz; Deptuch, Tomasz; Kępka, Cezary; Tyczyński, Paweł; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Since May 2005 a novel system of pre-hospital management of patients with suspected acute myocardial infarction (MI) is in operation in the eastern part of Masovia province. Thanks to recording of the ECG in the patient’s home by the ambulance staff and subsequent ECG teletransmission to the Institute of Cardiology (IK) in Warsaw (Anin), reliable, pre-hospital diagnosis of MI can be made which is followed by direct transport of the patient to IK by-passing the district hospital. At the time new equipment was purchased ambulance staff were encouraged to make wide use of teletransmission as this may shorten the time in which the patient reaches the interventional cardiology centre. Aim of the study was to assess the frequency of use of the new system. Material and methods: From a prospective registry the number of teletransmissions was established, as was the number of patients admitted to IK following teletransmission, separately for each transmitter and month. From a prospective database of invasive procedures in IK the total number of STEMI patients who underwent emergent coronary angiography in each month was established. Detailed analysis was performed for the period May-October 2006. Results: Between May 2005 and October 2006 ECGs of the total of 856 patients were transmitted, from which 267 patients with acute coronary syndrome were admitted (including 214 STEMI patients). Between May and October 2006 there were 376 teletransmissions and 129 admissions, respectively. On the average 32% of teletransmissions resulted in admission of the patient to IK; this rate tended to increase as the programme continued. The percentage of STEMI patients admitted to IK following teletransmission in relation to the total number of STEMI patients admitted to IK was similar in each month and averaged 30%. For the whole area were the programme was conducted the incidence of STEMI patients referred for treatment in IK based on ECG teletransmission was 13/100,000 inhabitants/year (ranging from 3 to 55 per 100,000 inhabitants per year in various districts). Conclusions: 1. Within the framework of the pilot programme ECG teletransmission was effectively introduced to pre-hospital management of patients with suspected acute myocardial infarction. 2. As the programme continues the use of teletransmission becomes increasingly rational. 3. Frequency of use of the ECG teletransmission varies significantly between districts and probably depends on motivation of individual ambulance teams and on percentage of ambulances capable of ECG teletransmission.